2019
DOI: 10.1021/acs.est.9b03374
|View full text |Cite|
|
Sign up to set email alerts
|

Polyaniline: A New Metal-Free Catalyst for Peroxymonosulfate Activation with Highly Efficient and Durable Removal of Organic Pollutants

Abstract: Metal-free heterogeneous catalysts are receiving more and more attention for wastewater remediation by activating peroxymonosulfate (PMS) due to their environmental benign. However, carbon-based materials as the most typical metal-free heterogeneous always suffer from poor durability. Inspired by the fact that a conjugated system may facilitate the electron transfer during PMS activation, we innovatively select polyaniline (PANI) as a new PMS activator and investigate its catalytic performance in detail. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(15 citation statements)
references
References 86 publications
1
14
0
Order By: Relevance
“…To further validate whether the carbonyl group in NCN-900 is responsible for the generation of 1 O 2 via PMS activation, the detection of 1 O 2 in the NCN-900/PDS system was performed considering that the carbonyl group was proven to be capable of activating PDS to yield 1 O 2 . , Seen from Figure a, no characteristic signals of 1 O 2 are noted in the EPR spectrum of NCN-900/PDS, excluding the role of the carbonyl group in PMS activation over NCN-900 for 1 O 2 formation. In addition, a very recent work demonstrated that the main origin of 1 O 2 in the course of PMS activation by the polyaniline catalyst was the self-decomposition of PMS. However, the aforementioned results in terms of (i) the observably enhanced BPA oxidation and 1 O 2 production in the NCN-900/PMS system in D 2 O as compared with those in H 2 O (see Figure S8) and (ii) the significant inhibition of BPA degradation over NCN-900 by PMS activation in the presence of a rather low concentration of β-carotene (see Figure e) confirm the generation of 1 O 2 in the NCN-900/PMS system originates from PMS activation by NCN-900 instead of PMS self-decomposition.…”
Section: Resultsmentioning
confidence: 99%
“…To further validate whether the carbonyl group in NCN-900 is responsible for the generation of 1 O 2 via PMS activation, the detection of 1 O 2 in the NCN-900/PDS system was performed considering that the carbonyl group was proven to be capable of activating PDS to yield 1 O 2 . , Seen from Figure a, no characteristic signals of 1 O 2 are noted in the EPR spectrum of NCN-900/PDS, excluding the role of the carbonyl group in PMS activation over NCN-900 for 1 O 2 formation. In addition, a very recent work demonstrated that the main origin of 1 O 2 in the course of PMS activation by the polyaniline catalyst was the self-decomposition of PMS. However, the aforementioned results in terms of (i) the observably enhanced BPA oxidation and 1 O 2 production in the NCN-900/PMS system in D 2 O as compared with those in H 2 O (see Figure S8) and (ii) the significant inhibition of BPA degradation over NCN-900 by PMS activation in the presence of a rather low concentration of β-carotene (see Figure e) confirm the generation of 1 O 2 in the NCN-900/PMS system originates from PMS activation by NCN-900 instead of PMS self-decomposition.…”
Section: Resultsmentioning
confidence: 99%
“…Ethanol (EtOH) with α‐H is an excellent radical scavenger for both •OH ( k = (1.2–2.8) × 10 9 mol −1 s −1 ) and SO 4 •− ( k = (1.6–7.7) × 10 7 mol −1 s −1 ), whereas tert‐butyl alcohol (TBA) without α‐H is only effective for •OH ( k = (3.8–7.6) × 10 8 mol −1 s −1 ) but not for SO 4 •− ( k = (4.0–9.1) × 10 5 mol −1 s −1 ). [ 33 ] As Figure 4f, the addition of TBA weakly inhibited BPA elimination while the introduction of EtOH significantly depressed the removal ratio of BPA in 8 min from 97.65% to 58.99%, which meant that SO 4 •− rather than •OH was the dominant radical responsible for BPA degradation. Moreover, KI was used as another quencher to probe the existence of surface‐bound radicals.…”
Section: Resultsmentioning
confidence: 99%
“…•− (k = (1.6-7.7) × 10 7 mol −1 s −1 ), whereas tert-butyl alcohol (TBA) without α-H is only effective for •OH (k = (3.8-7.6) × 10 8 mol −1 s −1 ) but not for SO 4 •− (k = (4.0-9.1) × 10 5 mol −1 s −1 ). [33] As Figure 4f, the addition of TBA weakly inhibited BPA elimination while the introduction of EtOH significantly depressed the removal ratio of BPA in 8 min from 97.65% to 58.99%, which meant that Table 1. Comparison of the BPA degradation efficiency by CoP@MOF-2-C with those by previously reported catalysts through PMS activation.…”
Section: (6 Of 12)mentioning
confidence: 89%
“…As shown in Figure 4b, weak triplet signals of TEMP− 1 O 2 with the peak intensity ratio of 1:1:1 were observed in the PMS-alone solution, which is usually attributed to the self-decomposition of PMS. 48 With the addition of the MnFeO nanocubes, however, no substantial increase in the peak intensity was observed, and the peak intensity did not substantially decrease when p-ASA was present. These results indicate that 1 O 2 was also not a dominant ROS for the p-ASA oxidation.…”
Section: ■ Experimental Sectionmentioning
confidence: 94%